Editorial - Vlamos, Panagiotis (Epistēmēs Metron Logos, 2020)
A scientific journal is not just space where high-quality and peer-reviewed articles are published. Academics adjust the structure, the content and even the style of their papers according to the journal they wish to make their contribution. Therefore, journals create niches, form audiences and in the end, shape science itself. It is in this spirit that we publish EML journal; not just to create more available space to publish more articles, but to substantially contribute to the shaping of epistemology and philosophy in general; eventually of science itself. For this reason, on one hand, we stick to traditional processes such as a double-blind peer review or the classic structure and referential system that is so well-known to the scientific community. On the other hand, we will introduce novelties that, we believe, are for the sake of progress. Our thoughts include the creation of an online community; application of new forms of peer-review; the establishment of new quality standards, based not so much in references or statistics, but in measurable logical cohesion of the arguments. We wish to remain true to our vision of science (epistēmē) and philosophy, but at the same time, be flexible enough so as to co-form the structure and the content of the EML journal based on scientific feedback.